BAFF/APRIL expression-guided telitacicept therapy demonstrates superior efficacy in systemic lupus erythematosus patients: a real-world comparative study - Huang, Li; Huang, Yingzi; Zeng, Jiamin; Zhang, Huhai; Chen, Liping; Li, Yi; Zhao, Hongwen; Tang, Xiaopeng (Frontiers in Medicine, 2025)
BackgroundBiological agents targeting B-cell pathways represent significant advances in systemic lupus erythematosus (SLE) management, yet optimal patient selection remains challenging. This study evaluated whether BAFF/APRIL expression testing could guide personalized treatment decisions in SLE patients.MethodsIn this real-world observational study, we compared two treatment strategies in 86 SLE patients: personalized therapy with telitacicept in BAFF/APRIL double-positive patients (n = 14) versus conventional belimumab therapy without expression testing (n = 72). Clinical responses, laboratory parameters, and steroid-sparing effects were assessed at 3 and 6 months.ResultsDespite having significantly higher baseline disease activity (SLEDAI 18.79 ± 9.34 vs. 8.86 ± 4.3) and more severe proliferative lupus nephritis (Class IV/IV + V in 78.6% vs. 52.8%), the BAFF/APRIL-guided telitacicept group achieved higher complete response rates (57.1% vs. 48.6%) and lower non-response rates (7.1% vs. 23.6%) compared to the conventional belimumab group. The BAFF/APRIL-guided group showed more substantial improvements in complement C3 levels (Δ = 0.49 vs. 0.24, p < 0.001) and anti-dsDNA antibody reduction (Δ = −177.07 vs −117.00, p = 0.028) at 6 months. Notably, normalization of immunological parameters was significantly better in the personalized therapy group, with dsDNA abnormalities decreasing from 92.9 to 7.1% (vs 91.7–32.5%) and C3 abnormalities from 100 to 28.6% (vs 91.7–61.1%). The BAFF/APRIL-guided group also achieved greater steroid dose reduction at 6 months (Δ = −35.00 vs −25.00 mg, p = 0.014).ConclusionBAFF/APRIL expression-guided telitacicept therapy demonstrated superior efficacy in improving clinical responses and laboratory parameters in SLE patients compared to conventional belimumab therapy, despite treating patients with more severe baseline disease. This real-world study provides preliminary evidence supporting BAFF/APRIL testing as a potential biomarker-driven approach for personalized SLE management, warranting further prospective validation.